Aggregate load profile and decarbonization: Impacts of actionable demand drivers in New York. (July 2022) - Pineau, P.-O.; Caron-Perigny, P.-O.; Tarel, G.J.; Borelle, A.; Pollux, L.
Abstract: In a decarbonized future, electricity will likely play a much greater role in all aspects of the economy, while power generation will increasingly rely on intermittent sources such as wind and solar. In deep decarbonization studies of power systems, the most striking conclusions are usually on the generation side: the need of tens of GW of new clean generation capacities and storage are typical conclusions. However, these conclusions are the direct consequence of electricity demand projections, which usually get less attention and sometimes lack detailed explanation. At the very least, these projections are aggregated and suffer from a deficit of transparency in their methodology. A detailed knowledge of possible future load profiles, and how the evolution of their drivers influences their shape, is therefore very important to plan adequately energy and power requirements, as well as regional interconnections and storage. This paper uses a bottom-up approach based on the useful energy consumed in the residential, commercial, transportation and industrial sectors to explore the load profile sensitivity to key parameters. This approach is then used to provide hourly load profiles for a full year for the state of New York as an illustration. The impact of these key parameters is demonstrated through three scenarios: business as usual, accelerated electrification and energy efficiency breakthrough. Policy makers, planning for very ambitious penetration level of renewable energy generation capacity have to take into account the effect on electricity peak and total demand of their energy efficiency initiatives. Highlights: Load profiles are the starting point of power system planning. The forecast literature on load profiles does not focus on actionable demand drivers. Our bottom-up model illustrates how radically different load shapes can be. By 2040, New York could evolve towards a 54 GW peak or a 25 GW one. Energy efficiency in buildings and EV charging profile are actionable drivers.